Bark and Grape Microbiome of Vitis vinifera: Influence of Geographic Patterns and Agronomic Management on Bacterial Diversity - Vitulo, Nicola; Lemos, Wilson José Fernandes; Calgaro, Matteo; Confalone, Marco; Felis, Giovanna E.; Zapparoli, Giacomo; Nardi, Tiziana (Frontiers in Microbiology, 2019)
In recent years, the concept of “microbial terroir” has been introduced in the frame of the more renowned notion of “vitivinicultural terroir’, since several studies demonstrated that wine characteristics are related to regional microbial community compositions. Most of the existing research focused on grape berries microbiota, since it can directly impact wine quality. In this work we studied, for the first time through next-generation sequencing, the epiphytic bacterial community of vine bark and its relationships with grape microbiota. The study was carried out in two Italian wine appellations (situated in different regions) to explore the impact of biogeography, and the influence of two agronomical practices (biodynamic and conventional) was evaluated as well. Overall, our results show that grapevine bark harbors a rich epiphytic microbiota and displays a higher microbial biodiversity than grape berry. Moreover, this study suggests that geographic and anthropogenic factors impact both bark and grape bacteriomes, but to a different extent. The evidence of a “microbial terroir” seems to be even more marked in bark than in berries, possibly due to its permanence over time and to its physical proximity with soil. The importance of vine trunk bark, as potential source of inoculum for grapes and as interesting bacterial diversity habitat, is evidenced. This opens new fields of investigation, not only for researchers that aim at describing this little-known habitat within the vineyard, but also for stakeholders from the wine industry that want to understand the roles of microorganisms on the entire winemaking process, from vineyard to cellar.